1990
DOI: 10.1002/per.2410040404
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in personality: Biological and/or psychological?

Abstract: The results of three empirical studies are reported in which the hypothesis is tested that diferences in personality variables between the morphophenotype sexes can be explained by psychological sex-role orientation variables. Furthermore, it was expected that normative sex-role orientations (measured with the SRO-Sand the A WS-S Scales) and gender-related self-concepts (femininity, masculinity, and androgyny measured with a modijied BSRI) explain more variance in personality variables than morphophenotype sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 19 publications
4
13
0
Order By: Relevance
“…First, the gender differences observed for the total scores and sub-dimensions of DT traits provide partial support for Hypothesis 1. The results for psychopathy and Machiavellianism traits are in line with those found in the previous literature (Muris et al, 2017;Jonason & Davis, 2018;Cale & Lilienfeld, 2002;Krampen et al, 1990). The higher psychopathy scores found in men in comparison with women are compatible with scientific evidence showing that in general men present more antisocial behaviours due to social or genetic factors (Cale & Lilienfeld, 2002;Book, Starzyk, & Quinsey 2001;Reidy, Shirk, Sloan, & Zeichner, 2009).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…First, the gender differences observed for the total scores and sub-dimensions of DT traits provide partial support for Hypothesis 1. The results for psychopathy and Machiavellianism traits are in line with those found in the previous literature (Muris et al, 2017;Jonason & Davis, 2018;Cale & Lilienfeld, 2002;Krampen et al, 1990). The higher psychopathy scores found in men in comparison with women are compatible with scientific evidence showing that in general men present more antisocial behaviours due to social or genetic factors (Cale & Lilienfeld, 2002;Book, Starzyk, & Quinsey 2001;Reidy, Shirk, Sloan, & Zeichner, 2009).…”
Section: Discussionsupporting
confidence: 90%
“…Firstly, in relation to psychopathy, both in clinical and community samples, this trait has shown to be much stronger in men than in women (e.g., Cale & Lilienfeld, 2002, Nicholls, Ogloff, Brink, & Spidel, 2005. Secondly, although there are few studies analysing the relationship between Machiavellianism and gender, these have also shown higher scores for men than women (e.g., Krampen, Effertz, Jostock, & Müller, 1990). Finally, through a meta-analysis in which 355 studies were included, Grijalva et al (2015) found that men scored higher than women on narcissism.…”
Section: Introductionmentioning
confidence: 99%
“…Brown et al., 1986; Hammen, 1991; Hammen et al., 1986) and negatively linked to internal locus of control, while women are more frequently affected by negative life events than men (see also Dalgard et al., 2006; Marcotte et al., 2002; McIntosh, Keywell, Reifman, & Ellsworth, 1994). Internal locus of control is negatively connected to depression (in accordance with Bandura, 1986; Krampen, 1991 and Seligman, 1975), and women have lower internal loci of control than men (see also Krampen, 1991; Krampen et al., 1990 and Nolen‐Hoeksema et al., 1999). Above that, traditional normative SRO has a negative impact on internal locus of control in women but not in men.…”
Section: Discussionmentioning
confidence: 58%
“…However, the effect sizes of gender differences are too small to substantially account for gender differences in depression. Interestingly, gender role identity (masculinity, femininity, androgyny) and normative sex‐role orientation (SRO) explain more variance in control and competence beliefs than gender (Krampen, 1991; Krampen, Effertz, Jostock, & Müller, 1990).…”
Section: Locus Of Control Beliefsmentioning
confidence: 99%
“…A lot of psychological theories have provided explanation to what constitute gender differences. The psychology literature is filled with consistent empirical findings indicating sex differences between male and female's personality (Krampen, Effertz, Jostock & Muller;1990). For instance, many empirical findings reported that girls or women show higher score in trait anxiety than boys and men which could give a signal on their reaction to traumatic events.…”
Section: Introductionmentioning
confidence: 99%